Oligomer-salt derived 3D, heavily nitrogen doped, porous carbon for Li-ion hybrid electrochemical capacitors application - Gokhale, Rohan; Aravindan, Vanchiappan; Yadav, Prasad; Jain, Srashti; Phase, Deodatta; Madhavi, Srinivasan; Ogale, Satishchandra (Carbon, 2014)
3D high surface area porous carbon is seen to form via self assembly of porous graphene sheets by direct pyrolysis of an oligomer salt tailored for the realization of molecular level activation. The oligomer salt was derived from 4-amino benzoic acid as the monomer by a facile free radical polymerization process. Incorporation of the functional groups (-COONa) eliminate the need for any external activating agents (KOH, ZnCl2, etc.) and also render high degree of sub-nanoscale homogeneity. This oligomer derived carbon (ODC) exhibits efficient performance in non-aqueous charge storage application namely Li-ion hybrid electrochemical capacitor (Li-HEC) owing to its high surface area, 3D interconnectivity and an appropriate pore size distribution. The Li-HEC fabricated with ODC based electrodes delivered a maximum energy density of similar to 63 Wh kg(-1) with spinel L4Ti5O12 as the anode. (C) 2014 Elsevier Ltd. All rights reserved.

Orthorhombic/cubic Cd2SnO4 nanojunctions: enhancing solar water splitting efficiency by the suppression of charge recombination - Deshpande, Aparna; Kelkar, Sarika A.; Rayalu, Sadhana; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
The low practical efficiency of binary metal oxide semiconductor-based photo-electrochemical (PEC) water splitting has prompted researchers to examine ternary and quaternary oxides, which provide more leverage for engineering the desired PEC properties via stoichiometry (valence) and phase control. One ternary system of interest in this context is cadmium tin oxide (Cd2SnO4), which supports the cubic and orthorhombic phases with optical, electronic and catalytic properties that are favourable for PEC water splitting. However, its practical PEC performance is limited by high surface recombination of the photogenerated charge carriers. In this work we circumvent this problem by engineering the constitution of Cd2SnO4 nanoparticles to a biphasic nanojunction form, comprising of a nanocomposite of cubic and orthorhombic phases. The favourable conduction band alignment between the cubic and orthorhombic phases leads to a dramatic reduction in the recombination of the photogenerated charges, leading to a 10-fold increase (from 250 mu A cm(2) to over 2 mA cm(2)) in the photocurrent vis-a-vis the single cubic or orthorhombic phase performance. We discuss the underlying mechanism for the observed dramatic enhancement in the water splitting efficiency.

Organic-inorganic perovskitoid with zwitterion cysteamine linker and its crystal-crystal transformation to ruddlesden-popper phase - Kour, Prachi; Reddy, Mallu Chenna; Pal, Shiv; Sidhik, Siraj; Das, Tisita; Pandey, Padmini; Mukherjee, Shatabdi Porel; Chakraborty, Sudip; Mohite, Aditya D.; Ogale, Satishchandra (Angewandte Chemie-International Edition, 2021)
We demonstrate synthesis of a new low-D hybrid perovskitoid (a perovskite-like hybrid halide structure, yellow crystals, P21/n space group) using zwitterion cysteamine (2-aminoethanethiol) linker, and its remarkable molecular diffusion-controlled crystal-to-crystal transformation to Ruddlesden-Popper phase (Red crystals, Pnma space group). Our stable intermediate perovskitoid distinctly differs from all previous reports by way of a unique staggered arrangement of holes in the puckered 2D configuration with a face-sharing connection between the corrugated-1D double chains. The PL intensity for the yellow phase is 5 orders higher as compared to the red phase and the corresponding average lifetime is also fairly long (143 ns). First principles DFT calculations conform very well with the experimental band gap data. We demonstrate applicability of the new perovskitoid yellow phase as an excellent active layer in a self-powered photodetector and for selective detection of Ni2+ via On-Off-On photoluminescence (PL) based on its composite with few-layer black phosphorous.
Keywords: Crystal growth; organic-inorganic hybrid composites; perovskite phases; photodetectors; zwitterions